First polychlorinated biphenyls (PCBs) monitoring in seawater, surface sediments and marine fish communities of the Persian Gulf: Distribution, levels, congener profile and health risk assessment. (October 2019) - Ranjbar Jafarabadi, Ali; Riyahi Bakhtiari, Alireza; Mitra, Soumita; Maisano, Maria; Cappello, Tiziana; Jadot, Catherine
Abstract: Polychlorinated biphenyls (PCBs) are persistent organic pollutants that, due to their high toxicity, lipophilic property and widespread dispersal in the global environment, present a danger for human health and ecological systems. Although the inventory and use of PCBs are extensively reported worldwide, the status of PCBs in Iran is still unknown. In this study, the concentrations of PCBs were determined in the environmental matrices and in five commercially important fish species from Larak coral Island, Persian Gulf, Iran, in winter and summer 2015. A positive correlation was found among PCBs levels and congeners profiles in seawater (0.97–3.10 ng L −1 ), surface sediments (2.95–7.95 ng g −1 dw) and fish samples (7.20–90.19 ng g −1 dw), indicating fish as suitable bioindicator of environmental PCBs contamination. In all matrices, a high contribution of light and medium chlorinated congeners was detected in both seasons. In fish, the higher PCBs levels were found for both sexes in both seasons in liver and kidney than other tissues (skin, gonad, muscle) due to their high lipid content and PCBs lipophilicity. More importantly, the risks for human health associated with fish consumption were also evaluated, and it was found that all the toxicity indices measured for PCBs were within the World Health Organization (WHO) permissible limit of food consumption. However, it is highly recommended to inform the local population about potential risks attributable to dietary incorporation of locally caught fish, and establish a surveillance monitoring programme on PCBs in this region. Graphical abstract: Image 1 Highlights: PCBs levels were measured in environmental matrices and fish species from Larak, Iran. A positive correlation among all matrices indicate fish as suitable bioindicator of PCBs. A positive correlation between sediment and seawater parameters and PCBs was found. Human health risks for PCBs associated with fish consumption was low. Abstract : This is the first report on the levels and congeners profiles of PCBs in the environmental matrices and in five commercially important fish species from Larak Island, Persian Gulf, Iran, and their associated human health risks.